Developing science inquiry skills in early childhood through coding games - Munawar, Muniroh; Roshayanti, Fenny; Setyoady, Yuris; Afif Luthfy, Perdana; Happy, Nurina (LPMPP Universitas Negeri Yogyakarta, 2025)
The 21st century requires education to equip students not only with academic knowledge but also with such as innovation, productivity, reasoning, programming, data literacy, problem-solving, and critical thinking, to face the rapid global changes. This study aims to develop science inquiry skills from early childhood to support children in mastering the competencies needed in the 21st century. The research employed a descriptive qualitative design. Data were collected from 16 preschools through observations, interviews, and documentation. NVivo was used for data management and analysis. NVivo is a software application that assist researchers in organizing, analyzing, and visualizing qualitative data. The results reveal that coding games can foster seven core science inquiry skills: arguing based on existing evidence, identifying problems, analyzing and interpreting data, evaluating and communicating, planning and conducting investigations, asking questions, and constructing explanations. This research recommends that more preschools integrate coding games into their learning activities, as they can effectively enhance children’s science inquiry skills, which are essential for their future academic and professional success.